2017
DOI: 10.2217/cer-2016-0087
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and stress severities in multiple sclerosis patients using injectable versus oral treatments

Abstract: Mild anxiety was higher among interferon users, which could be due to injection anxiety reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Since no instrument has been designed in Iran so far to evaluate the disease-specific problems and to evaluate the feedback to health personnel in a semi-structured model of problems identification and care planning, it was crucial to develop and validate an instrument used to evaluate the important dimensions of the disease-specific problems and to provide an opportunity for giving feedback to health personnel. Different studies have previously used various questionnaires to assess the problems of patients with MS such as the measurement of fatigue using FSS scale [38]; stress, anxiety, and depression using DSAA 21 scale [39]; and physical problems using several questionnaires [12,40,41]. It was indicated that the MSPQ scale could be used to evaluate all the disease-specific problems, including physical, psychological, emotional, family, and socio -economic problems in patients with MS in a single questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Since no instrument has been designed in Iran so far to evaluate the disease-specific problems and to evaluate the feedback to health personnel in a semi-structured model of problems identification and care planning, it was crucial to develop and validate an instrument used to evaluate the important dimensions of the disease-specific problems and to provide an opportunity for giving feedback to health personnel. Different studies have previously used various questionnaires to assess the problems of patients with MS such as the measurement of fatigue using FSS scale [38]; stress, anxiety, and depression using DSAA 21 scale [39]; and physical problems using several questionnaires [12,40,41]. It was indicated that the MSPQ scale could be used to evaluate all the disease-specific problems, including physical, psychological, emotional, family, and socio -economic problems in patients with MS in a single questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Some AEs that potentially indicate centrally mediated effects, such as depression and anxiety, have also been reported; however, MS patients frequently present with anxiety and depression, i.e., these have been reported in over 20% of MS patients (Marrie et al 2015 ). In several studies and 1 meta-analysis, fingolimod and other disease-modifying therapies (DMTs) for MS had no significant association with the onset of anxiety, depression, or other neuropsychiatric events (Al-Hussain et al 2017 ; Gasim et al 2018 ; Moreau et al 2017 ; Tauil et al 2018 ). In a subset of 141 African-American RRMS patients from a randomized open-label study, fingolimod (0.5 mg/day) was associated with a lower AE rate (AEs per patient-year) compared with injectable DMTs for anxiety (0.055 vs. 0.161) and depression (0.092 vs. 0.134) (Cascione et al 2018 ).…”
Section: Clinical Ae Data Suggestive Of Abuse or Dependence Potentialmentioning
confidence: 99%
“…39 The issues associated with beta Interferon-1B injection are suggested to be responsible for inducing anxiety and stress in MS patients. 40 Depression and fatigue are other common symptoms facing MS patients; however, symptomatic management might increase patients' adherence to beta Interferon-1B treatment. 40 For decades, beta Interferon-1B treatment has proved to be effective in the management of relapsing MS, and it has been used in several clinical trials as a reference treatment to test the efficacy of newer MS DMTs.…”
Section: Teriflunomidementioning
confidence: 99%